Differentiation potential of individual olfactory c‐Kit+ progenitors determined via multicolor lineage tracing. Issue 3 (10th June 2015) - Goss, Garrett M.; Chaudhari, Nirupa; Hare, Joshua M.; Nwojo, Raphael; Seidler, Barbara; Saur, Dieter; Goldstein, Bradley J.
ABSTRACT: Olfactory tissue undergoes lifelong renewal, due to the presence of basal neural stem cells. Multiple categories of globose basal stem cells have been identified, expressing markers such as Lgr5, Ascl1, GBC‐2, and c‐Kit. The differentiation potential of individual globose cells has remained unclear. Here, we utilized Cre/loxP lineage tracing with a multicolor reporter system to define c‐Kit+ cell contributions at clonal resolution. We determined that reporter expression permitted identification of c‐Kit derived progeny with fine cellular detail, and that clones were found to be comprised by neurons only, microvillar cells only, microvillar cells and neurons, or gland/duct cells. Quantification of reporter‐labeled cells indicated that c‐Kit+ cells behave as transit amplifying or immediate precursors, although we also found evidence for longer‐term c‐Kit+ cell contributions. Our results from the application of multicolor fate mapping delineate the clonal contributions of c‐Kit+ cells to olfactory epithelial renewal, and provide novel insight into tissue maintenance of an adult neuroepithelium. © 2015 Wiley Periodicals, Inc. Develop Neurobiol 76: 241–251, 2016